Strategi Pengelolaan Sampah yang Efektif di Masyarakat - Lisa Dwi Afri; Fauziah Mawaddah Harefa; Meri Muliani Hasibuan; Nazira Ananda; Putri Ramadani; Wahyu Wahono (Masyarakat Berkarya : Jurnal Pengabdian dan Perubahan Sosial, 2024)
The lack of waste management in the community of Kampung Benar Dusun VI Village, Kota Pari, Pantai Cermin District, Serdang Bedagai Regency is due to the limited knowledge and understanding of waste management in general. People still think that waste management is not important because people think that their waste will decompose by itself without thinking that this will have a huge impact if the waste continues to be left unmanaged. One way to support this waste management program is through a waste bank. A waste bank is a place that is used to make it easier for the public to sort waste, then the sorted waste will be deposited at a factory that makes crafts from waste or at a waste collection point. The aim of this research is to determine community knowledge regarding waste management, analyze existing waste management in the community and find out what strategies are effective for waste management. The method used by researchers is an integrated counseling method and systematic training. Data was collected by observing in the field and conducting in-depth interviews with informants. The results of the research show that after providing outreach to the community that waste management is important, the community also understands better about good waste management and knows effective waste management strategies to implement using the 3R system.